Design and synthesis of chitosan/calcium lignosulfonate/Au NPs: Its performance for reduction of nitro compounds and in the treatment of cancer - Ruyi Xie; Jianming Zhou; Ting Wang; Yuan Xu; Bei Zhang; Sally Negm; Attalla F. Elkott (Arabian Journal of Chemistry, 2024)
This work introduces the preparation of a novel type of crosslinked polymers support based on calcium lignosulfonate-chitosan (CLS-CS) hydrogel with capping/reducing ability to encapsulated gold nanoparticles (CLS-CS/Au NPs). The morphology, structure and physicochemical properties of the prepared nanoparticles were characterized by different analytical techniques such as FT-IR, FE-SEM, TEM, EDX-elemental mapping study. The obtained results shown that CLS-CS/Au NPs prepared as spherical particles with sizes of 20–30 nm. The CLS-CS/Au NPs was applied as well for reduction of nitroarenes. The reduction of nitroarenes was obtained with good to high yields within short times. The related nanocatalyst was recovered for eight runs without significant loss of its catalytic performance. The MTT examination was conducted to check the anti-pancreatic cancer, anti-gastric cancer, anti-colorectal carcinoma, and cytotoxicity efficacies of the treated cells with CLS-CS/Au NPs over a 48-hour period on normal (HUVEC) and cancer cells. The IC50 values of the CLS-CS/Au NPs were found to be 169 µg/mL for HT-29 (colorectal carcinoma cell), 196 µg/mL for MKN45 (Gastric cancer cell), and 112 µg/mL for PANC-1 (Pancreatic cancer cell). The growth of malignant colorectal, gastric and pancreatic cells was found to decrease in a dose-dependent manner when exposed to CLS-CS/Au NPs. Following clinical research, CLS-CS/Au NPs shows promise as an effective treatment for colorectal, gastric and pancreatic cancers.